2009
DOI: 10.1007/s00432-009-0617-1
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of high-risk human papillomavirus type HPV16 infection by ‘Praneem’ polyherbal tablet in women with early cervical intraepithelial lesions

Abstract: Our results showed for the first time that a 30-day intra-vaginal application of the Praneem can result in elimination of HPV infection from the uterine cervix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Currently, there is no HPV specific advanced therapy for treatment of cervical cancer. Recent studies have shown that anti-oxidants and herbal derivatives may be effective against prevailing HR-HPV infection but these leads are yet to prove their efficacy in preclinical and subsequent clinical studies [26-29]. …”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no HPV specific advanced therapy for treatment of cervical cancer. Recent studies have shown that anti-oxidants and herbal derivatives may be effective against prevailing HR-HPV infection but these leads are yet to prove their efficacy in preclinical and subsequent clinical studies [26-29]. …”
Section: Introductionmentioning
confidence: 99%
“…We had earlier made a microbicide named "Praneem" which had undergone similar trials in women at early stage of HPV 16 infection as reported elsewhere [7]. After 30 days of use of Praneem, 6 out of 10 subjects showed the elimination of HPV 16.…”
Section: Discussionmentioning
confidence: 91%
“…Based on safety of herbal ingredients and their general anti-microbicidal action, a few poly-herbal formulations or mixtures based on herbal derivatives have been evaluated in clinical studies. Praneem, a combination of leaf extract of Azadirachta indica, saponins, purified extracts of Emblica officinalis, Mentha citrata oil, and extracts of Aloe vera gel was examined in HPV infected women in a placebo controlled clinical study (208). One course of thirty day intra-vaginal application of Praneem polyherbal tablet in women with early cervical intraepithelial lesions resulted in elimination of HPV16 infection in 60% of the women (6/10).…”
Section: Amongmentioning
confidence: 99%